Effects of composts from co-composting of tree pruning waste, cow dung, and biomass fly ash on soil acidity neutralization and growth of Chinese cabbage - Somjai Karnchanawong (2018)
The objective of this research was to determine the application effects of compost produced from tree pruning waste and cow dung amended with biomass fly ash on soil acidity neutralization and Chinese cabbage growth. The acid soils were mixed with six different composts and fly ash, namely, Run 1-6: soil+composts produced from tree pruning waste, cow dung amended with fly ash ranged from 0% (control) to 4%, 8%, and 12%; Run 5: soil+control compost+fresh fly ash; and Run 6: soil+fresh fly ash. Thereafter, they were cured and placed in ten replicated diameter pots for growing Chinese cabbage (Brassica chinensis var. parachinensis). The composite samples of soils during curing and planting were taken and analyzed for their pH, exchangeable hydrogen, and aluminum ions. The height and weight of each vegetable were determined. The results showed that both fly ash and compost can neutralize the acid soil and decrease the quantity of exchangeable hydrogen and aluminum ions. The maximum growth of the Chinese cabbage was found in the soil mixed with the compost produced from compost mixes amended with 8% fly ash. © (2014) Trans Tech Publications, Switzerland.